Kinship Terms of the Mongush Tribal Group of the Village of Ayangaty in the Barun-Khemchik District - Suvandii, Nadezhda D. (The New Research of Tuva, 2021)
The article examines the terminology of kinship and blood relations of the Tuvans drawing on the case of terms used by the Mongush tribal group, the natives of the Sumon of Ayangata in the Barun-Khemchik district. They call their kinship community not only ‘tөrel aimag’ (‘tribal group’) but also by the term ‘tөrel-dөrgul mongushtar’ (‘relatives of the Mongush people’). The material was collected by the author during one of the clannish gatherings in 2021, which was held in order to perform the sug bazhyn dagylgazy — the ‘rite of consecration of the spring’s source’, including through interviews with representatives of the group, i.e. relatives. In the article, the terminology is presented in the following groups: general terms of kinship, special terms for designating blood relatives and relatives-in-law. The collected terms allow us to see that traditional terminology is important for the older generation. It is included in dictionaries and studied by researchers. Young people and children use many Russian terms. In addition, there is a group of neologisms. Modern people are not satisfied with established designations. They do not try to comply with the norms and prefer to use words that are more convenient or interesting to them, and sometimes those that have diminutive endings. The kinship terminology of one kin group of the Western Tuvans is of research interest per se, because it shows both the general Tuvan trends in the language development and certain local features. Nevertheless, in order to have the overall picture, it is necessary to expand the research field and include other kin groups in it.